Paradoxical effects of brain death and associated trauma on rat mesenteric microcirculation: an intravital microscopic study - Simas, Rafael (Hospital das Clínicas da Faculdade de Medicina da Universidade de São Paulo, 2012)
OBJECTIVE: Experimental findings support clinical evidence that brain death impairs the viability of organs for transplantation, triggering hemodynamic, hormonal, and inflammatory responses. However, several of these events could be consequences of brain death–associated trauma. This study investigated microcirculatory alterations and systemic inflammatory markers in brain-dead rats and the influence of the associated trauma. METHOD: Brain death was induced using intracranial balloon inflation; sham-operated rats were trepanned only. After 30 or 180 min, the mesenteric microcirculation was observed using intravital microscopy. The expression of P-selectin and ICAM-1 on the endothelium was evaluated using immunohistochemistry. The serum cytokine, chemokine, and corticosterone levels were quantified using enzyme-linked immunosorbent assays. White blood cell counts were also determined. RESULTS: Brain death resulted in a decrease in the mesenteric perfusion to 30%, a 2.6-fold increase in the expression of ICAM-1 and leukocyte migration at the mesentery, a 70% reduction in the serum corticosterone level and pronounced leukopenia. Similar increases in the cytokine and chemokine levels were seen in the both the experimental and control animals. CONCLUSION: The data presented in this study suggest that brain death itself induces hypoperfusion in the mesenteric microcirculation that is associated with a pronounced reduction in the endogenous corticosterone level, thereby leading to increased local inflammation and organ dysfunction. These events are paradoxically associated with induced leukopenia after brain damage.